7B-2=8(B+3)

Simple and best practice solution for 7B-2=8(B+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7B-2=8(B+3) equation:


Simplifying
7B + -2 = 8(B + 3)

Reorder the terms:
-2 + 7B = 8(B + 3)

Reorder the terms:
-2 + 7B = 8(3 + B)
-2 + 7B = (3 * 8 + B * 8)
-2 + 7B = (24 + 8B)

Solving
-2 + 7B = 24 + 8B

Solving for variable 'B'.

Move all terms containing B to the left, all other terms to the right.

Add '-8B' to each side of the equation.
-2 + 7B + -8B = 24 + 8B + -8B

Combine like terms: 7B + -8B = -1B
-2 + -1B = 24 + 8B + -8B

Combine like terms: 8B + -8B = 0
-2 + -1B = 24 + 0
-2 + -1B = 24

Add '2' to each side of the equation.
-2 + 2 + -1B = 24 + 2

Combine like terms: -2 + 2 = 0
0 + -1B = 24 + 2
-1B = 24 + 2

Combine like terms: 24 + 2 = 26
-1B = 26

Divide each side by '-1'.
B = -26

Simplifying
B = -26

See similar equations:

| 5(v-1)=4 | | 2x-47+x=112 | | 7+c+12=-4c+12 | | 1=6(k+5) | | 7(x-4)=3(x-8) | | 4x+3=57-2x | | 2x-47=2(53)-47 | | 6r+11=15-r | | x^2+4x-94=0 | | 4-2(x+5)=4 | | 7(b-2)=4 | | 2(10-3d)+80= | | 3x+2-x=12 | | F(x+8)=3(x+8)-9 | | 7=8(r-6) | | 7(v+4)-3v=2(2v+2)-12 | | 0.04x^2-3.5x+100=10 | | 8x+17=5x+23 | | 18x+54=252 | | y=0.7x-3.6 | | 10+11x=-30+x | | -6(i-3)=2 | | 4x+6(x-4)=16 | | 22+4x=9x+2 | | -9(-6)-5(2)=12 | | 154x=462 | | -9(3)-5(-6)=12 | | 5x+5y+6z-2x+z-8y= | | 4=7(r-3) | | -36=3(x-3)-6x | | 4-5y=-20 | | 9=6(q-6) |

Equations solver categories